2019
DOI: 10.1002/pat.4795
|View full text |Cite
|
Sign up to set email alerts
|

Studies on electro‐optical properties of polymer matrix/LC/ITO nanoparticles composites

Abstract: In this paper, polymer-dispersed liquid crystal (PDLC) films consisting of liquid crystal (LC)/monomers/indium tin oxide (ITO) nanoparticles with good near-infrared absorption property had been fabricated, and the influence of the ITO nanoparticles modified with 3-methacryloxypropyltrimethoxysilane (KH570) on the PDLC films was systematically studied. First, different liquid crystal content was studied to obtain PDLC films with good electro-optical properties. And then, various weight ratio of ITO nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The salient advantages of the presented protocol of incorporating the BN nanosheets into the polymer network visa `-vis the existing literature, have to be mentioned. Firstly, in cases where high IR reflection has been achieved, the system invariably contains explicitly IR emissive additives such as ITO 40,41 or ATO 42 nanoparticles, thus creating a materialbased limitation. In contrast, the present protocol achieves high IR modulation albeit employing IR-transparent components, including the BN nanosheets, bringing out the importance of the spatial placement of the nanostructures as the basis, and thus making it a generic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salient advantages of the presented protocol of incorporating the BN nanosheets into the polymer network visa `-vis the existing literature, have to be mentioned. Firstly, in cases where high IR reflection has been achieved, the system invariably contains explicitly IR emissive additives such as ITO 40,41 or ATO 42 nanoparticles, thus creating a materialbased limitation. In contrast, the present protocol achieves high IR modulation albeit employing IR-transparent components, including the BN nanosheets, bringing out the importance of the spatial placement of the nanostructures as the basis, and thus making it a generic approach.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] The nematic-based devices rely upon, with hardly an exception, the polymer dispersed liquid crystal (PDLC) architecture, and more importantly those distinctly containing IR-absorbing/scattering components. The devices do exhibit a desirable low-IR transmission, a feature not surprising since the system derives this property solely due to the presence of IR-emissive nanoparticles such as indium doped tin oxide (ITO), 40,41 antimony doped tin oxide (ATO), 42 and IR absorbing nanoparticles like Cs x WO 3 . 43 By their very nature, these filler structures do absorb IR and therefore could potentially cause undesirable internal heating upon exposure to direct sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Wu et al [ 71 ] of Nanjing University doped 1.5 wt% ITO powders of submicron size in the mixture (E7 + NOA65) and found that the operating voltages decreased due to the effects of ITO on the morphology of the PDLC as the anchoring force at the polymer/LC boundary was lowered. Recently Zhang et al [ 72 ] of Xijing University, China, also used ITO NPs with acrylate-based monomers after surface treatment of NP with 3-methacryloxypropyltrimethoxysilan. However, they found that the driving voltage was increased and CR was decreased with the increment of doping content at 0–20 wt% of NPs loading, while the near infra-red (NIR) absorption property of films was enhanced in the wavelength range of 1300 to 2500 nm.…”
Section: Preparation Of Nanoparticles Doped Pdlc Composite Filmmentioning
confidence: 99%
“…For example, researchers dope nanoparticles (NPs) like indium tin oxide (ITO) NPs, silica NPs, or inorganic NPs to original all-organic system to enhance the optical, thermal and mechanical stability of the polymer matrix and interaction with the LC and the change of permittivity of the LC droplets and the polymer matrix induced by the introduction of the NPs is also investigated. [20][21][22][23][24] Besides, the dye is also used to dope in the PDLC system to regulate many parameters of LC like refractive index, orientational order and dielectric constant due to the strong microscopic mutual interaction among the dye and LC molecules. [25][26][27][28] Moreover, carbon nanotubes (CNTs) are also successfully applied as dopants in PDLCs based on the anisotropic mechanical and electric properties resulted from the alignment of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an amount of work to improve the electro‐optical properties of the PDLC film by doping. For example, researchers dope nanoparticles (NPs) like indium tin oxide (ITO) NPs, silica NPs, or inorganic NPs to original all‐organic system to enhance the optical, thermal and mechanical stability of the polymer matrix and interaction with the LC and the change of permittivity of the LC droplets and the polymer matrix induced by the introduction of the NPs is also investigated 20–24 . Besides, the dye is also used to dope in the PDLC system to regulate many parameters of LC like refractive index, orientational order and dielectric constant due to the strong microscopic mutual interaction among the dye and LC molecules 25–28 .…”
Section: Introductionmentioning
confidence: 99%